Cây thuốc Việt Nam (Dược liệu chí VN) - Nguyễn, Văn Đàn (2011)
Tác giả: Nguyễn Văn Đàn, GS; Đòan Thị Nhu, PTS; Vũ Ngọc Lộ, PTS; Đỗ Huy Bích, DS; Bùi Xuân Chương, DS; Phạm Kim Mão, DS; Phạm Duy Mai, DS; Nguyễn Văn Tập; Trần Hưng; Trần Toàn -- Từ khóa: Cây thuốc; Dược liệu